Szociokulturális környezet, megküzdési stratégiák, életminőség (Szociológiai Szemle, 2024)
The aim of our study was to analyze the relationships between the coping strategies applied in work stress situations, the quality of life, and the social environment. The sample consisted of 343 working persons in two Hungarian regions that are fairly different in terms of economic development. Data were collected by a combination of questionnaire and interview techniques. Quality of life was defined on the basis of physical and psychological well-being of a person as well as some economic and cultural determinants of his environment. For the measurement of job-related coping strategies, the 16-item “Ways of Coping” questionnaire of Folkman and Lazarus was used. Hypotheses on the links between quality of life, social environment, and the coping strategies were confirmed by the method of Structural Equation Modeling. The factors that affected the quality of life differed in the two settlements. Problemcentered coping strategies had influences only in the economically disadvantageous village. We assume that both the nature of job-related problems and the efforts to solve them are more demanding in the poorer settlement and these disadvantages are mirrored in the worse quality of life in this village.